Weak Hadith in al-Qurtubi’s Legal Exegesis: A Critical Review of Surah al-Fatihah - Sakka, Abdul Rahman (QOF, 2025)
This study critically examines the utilisation of daif hadith in Al-Qurtubi’s tafsir ahkam, with particular emphasis on the interpretation of Surah al-Fatihah. Al-Qurtubi’s tafsir holds a significant and authoritative position within the field of tafsir, especially in the domain of tafsir ahkam, which has become a key reference in both classical and contemporary studies of legal exegesis. The aim of this article is to identify the daif hadith employed by Al-Qurtubi in his explanation of Surah al-Fatihah, assess their authenticity, and analyse the extent to which the incorporation of daif hadith influences the accuracy and authority of Qur'anic interpretation. By scrutinising Al-Qurtubi’s methodology for evaluating the credibility of hadith, this study highlights the impact of using daif hadith on the authority of interpretation, particularly in the formulation of legal decisions. The research adopts a qualitative-descriptive methodology, with data collected through a literature review. The hadith were traced using the takhrij method, their authenticity assessed through naqd al-sanad (chain of transmission criticism), and a critical analysis of Surah al-Fatihah was conducted. The results reveal that Al-Qurtubi used five daif hadith out of a total of twenty-one in his interpretation of Surah al-Fatihah, ranging from mild to severe daif. The employment of daif hadith demonstrates methodological inconsistencies in Al-Qurtubi’s approach. Several of these daif hadith diverge from the core teachings of Islam, suggesting that their inclusion has compromised the accuracy of his methodology, diminished his authority, and undermined the credibility of his tafsir, particularly as a legal exegesis.